2015
DOI: 10.1155/2015/608174
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidant Betanin Protects Rats from Paraquat-Induced Acute Lung Injury Interstitial Pneumonia

Abstract: The effect of betanin on a rat paraquat-induced acute lung injury (ALI) model was investigated. Paraquat was injected intraperitoneally at a single dose of 20 mg/kg body weight, and betanin (25 and 100 mg/kg/d) was orally administered 3 days before and 2 days after paraquat administration. Rats were sacrificed 24 hours after the last betanin dosage, and lung tissue and bronchoalveolar lavage fluid (BALF) were collected. In rats treated only with paraquat, extensive lung injury characteristic of ALI was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 47 publications
1
32
0
1
Order By: Relevance
“…Studies have investigated the capacity of betalains, mainly betanin, to scavenge free radicals in vitro, and this capacity is even higher than that of vitamin C [34,68]. Betanin has also been reported to inhibit cancer cell proliferation in vitro and in vivo [18], and it protects against acute lung injury and gastric lesions [30,69]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated the capacity of betalains, mainly betanin, to scavenge free radicals in vitro, and this capacity is even higher than that of vitamin C [34,68]. Betanin has also been reported to inhibit cancer cell proliferation in vitro and in vivo [18], and it protects against acute lung injury and gastric lesions [30,69]. …”
Section: Discussionmentioning
confidence: 99%
“…Acute lung injury (ALI) is a common disease with a high morbidity and mortality rate worldwide (1)(2). More than 2 million ALI cases caused by chemical poisoning including paraquat are reported annually in China, resulting in over 150,000 deaths (1).…”
Section: Introductionmentioning
confidence: 99%
“…It is an important source of phytochemicals, especially betacyanins . Mounting evidence has suggested that betacyanins possess free radical scavenging and antioxidant activities, which are closely associated with its protective effects against inflammation, atherosclerosis, and hyperlipidemia . Interestingly, red pitaya consumption has been reported to improve lipid profile and attenuate hyperinsulinemia and hyperglycemia in rats and type 2 diabetic subjects .…”
Section: Introductionmentioning
confidence: 99%